HATE SPEECH: PERSPEKTIF DAN ETIKA DI MEDIA SIBER - Musyaffa Musyafaa (Institut Agama Islam Negeri Bengkulu, 2017)
Hate Speech is termed hate speech. The sequence of words that make up the phrase. If viewed in terms of grammatically the speech is located as head (Main), and hate as a modifier (Explanation). It is clear that hate speech is a representation of the juridical aspect. In fact, it is part of a wide range of existing legislation. Not only Law No.11 / 2008 on ITE, but there are also articles of the Criminal Code and Civil Code. At least from the post-hate speech news circulating in the community, at least has reduced the intensity of speech hatred in the online media. Primarily, concerning the habit of some netizens doing a negative remark in the online media.